BRAIN STRUCTURE OF SHR RATS WITH GENETICALLY DETERMINED ARTERIAL HYPERTENSION - Aidarova, V.S.; Naumova, O.V.; Kudokotseva, O.V.; Lomakin, I.I.; Babiichuk, V.G. (World of Medicine and Biology, 2018)
To date, arterial hypertension (AH) is the most common cause of morbidity and mortality worldwide. An extremely important problem is the effect of high blood pressure (BP) on morphofunctional state of the brain. Spontaneously hypertensive SHR rats are characterized with genetically determined persistent high BP counts, that leads to the development of chronic hypertension, the course and consequences of those are close to the development of this disease in humans. Morphological and morphometric studies of the brain tissue derived from the precentral gyrus of 12-month-old SHR rats are presented. The samples were stained with hematoxylin and eosin, picrofusin by van Gieson and toluidine blue according to Nissl. The density of neurons, gliocytes and functioning (open) capillaries (in 1 mm2) in the layers III-V of the brain cortex was examined, and the value of the neuroglial index was calculated. Morphological and morphometric changes in the brain tissues of spontaneously hypertensive rats were found in a microscopic study. There was a thickening of the soft meninges due to their edema and excessive development of collagen fibers. Arterial vessels, as well as intracerebral arteries and arterioles, were characterized by uneven spasm, in the sites of which the typical accommodation of the endothelium in the form of a stockade and focal cell desquamation was noted, some small arteries and arterioles were the signs of wall hyalinosis. There was a thickening of the walls of the arteries resulted from o hypertrophy and hyperplasia of smooth muscle cells and excessive development of intermuscular collagen fibers. Part of the capillaries was with well-marked blood-filled lumens, another part was in a collapsed state and slightly discernible lumens, some of them were dilated with the signs of stasis. The tone of the vein walls was reduced, their lumens were widened and overfilled with blood. In a half of the observations, the veins with signs of erythrodiapedesis and the formation of focal perivascular hemorrhages were visualized. In all the observations in the brain cortex, there were found the sites wherein the laminar structure was disturbed. In all the layers of the cortex and subcortical formations, the neurons with ischemic changes were detected, numerous ghost cells were visualized. In the fine-grained, pale neuropil of the brain cortex, a diffuse increase in the density of gliocytes was observed with the formation of perivascular foci of the proliferation of hypertrophied astrocytes in the loci of cell rarefactions and desolations. In 40% of observations in the vision field, there were signs of plasma impregnation and fibrinoid necrosis of the artery wall, with formation mainly in the region of subcortical structures and white matter of diapedesis and small-focal hemorrhages, both acute and organized. In 30% of the observations in the cortex and subcortical structures, small ischemic infarcts occurred, partly with signs of organization. Morphometric examination of the III-V layers of brain cortex of the SHR rats showed a significant increase in the neuroglial index (1,48 ± 0,04) (due to a decrease in the density of neurons up to 1116,15 ± 41,97 cells/mm2 and increased density of neuroglia cells up to 1655,68 ± 52,26 cells/mm2) and decreased density of functioning capillaries (170,23 ± 7,01 cells/mm2), in comparison with the normotensive control (0,85 ± 0,02; 1473,09 ± 41,46; 1253,43 ± 45,33 and 228,81 ± 9,61, respectively), which may indicate the development of pathological changes at chronic hypertension not only in brain tissues, but also in the central nervous system as a whole.